Question
upstudy study bank question image url

Solve the equation by completing the square: \( x^{2}-12 x+56=3 \) \( \begin{array}{l}-6-\sqrt{17} i,-6+\sqrt{17} i \\ -6+17 i,-6-17 i \\ 6-17 i, 6+17 i \\ 0-\sqrt{17} i, 6+\sqrt{17} i \\ -17-\sqrt{3} i,-17+\sqrt{3} i\end{array} \)

Ask by Robbins Mcdonald. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = 6 + \sqrt{17} i \) and \( x = 6 - \sqrt{17} i \).

Solution

To solve the equation \( x^{2}-12 x+56=3 \) by completing the square, we will follow these steps: 1. **Rearrange the equation**: Move all terms to one side of the equation. \[ x^{2} - 12x + 56 - 3 = 0 \] This simplifies to: \[ x^{2} - 12x + 53 = 0 \] 2. **Complete the square**: We need to rewrite the quadratic in the form \( (x - p)^2 = q \). - Take the coefficient of \( x \), which is \(-12\), divide it by 2 to get \(-6\), and then square it to get \(36\). - Add and subtract \(36\) inside the equation: \[ x^{2} - 12x + 36 - 36 + 53 = 0 \] This can be rewritten as: \[ (x - 6)^{2} - 36 + 53 = 0 \] Simplifying gives: \[ (x - 6)^{2} + 17 = 0 \] 3. **Isolate the square**: \[ (x - 6)^{2} = -17 \] 4. **Take the square root of both sides**: \[ x - 6 = \pm \sqrt{-17} \] This can be expressed as: \[ x - 6 = \pm i\sqrt{17} \] 5. **Solve for \( x \)**: \[ x = 6 \pm i\sqrt{17} \] Thus, the solutions to the equation \( x^{2}-12 x+56=3 \) are: \[ x = 6 + i\sqrt{17}, \quad x = 6 - i\sqrt{17} \] Now, let's check the provided options: - The correct solutions are \( 6 + \sqrt{17} i \) and \( 6 - \sqrt{17} i \). Therefore, the correct answer is: \[ 6 + \sqrt{17} i, \quad 6 - \sqrt{17} i \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \( x^{2}-12 x+56=3 \) by completing the square, we start by rearranging it: 1. Move all terms to one side: \[ x^{2} - 12x + 56 - 3 = 0 \quad \Rightarrow \quad x^{2} - 12x + 53 = 0 \] 2. Next, isolate the quadratic and linear terms: \[ x^{2} - 12x = -53 \] 3. Complete the square on the left side. Take half of the coefficient of \( x \) (which is \(-12\)), square it, and add to both sides: \[ x^{2} - 12x + 36 = -53 + 36 \quad \Rightarrow \quad (x - 6)^{2} = -17 \] 4. Solve for \( x - 6 \) by taking the square root: \[ x - 6 = \pm \sqrt{-17} = \pm i\sqrt{17} \] 5. Finally, solve for \( x \): \[ x = 6 \pm i\sqrt{17} \] Hence, the solutions are: \[ 6 - i\sqrt{17} \quad \text{and} \quad 6 + i\sqrt{17} \] It looks like the options provided contain two solutions for \( x \); the correct representation would be \( \boxed{6 \pm i\sqrt{17}} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy